Finite Element Simulation of Vacuum Preloading at Palembang – Indralaya Toll Project - Herwan Dermawan; Bigman M. Hutapea; Endra Susila; Masyhur Irsyam (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Methods for the prediction of soil behavior during the application of vacuum preloading are available but have not been used precisely and have not been proven yet in Indonesia. There are two common approaches to vacuum preloading simulation, based on the application of a uniform external load to the vacuum area, and based on suddenly lowering the groundwater level to create vacuum conditions, respectively. This affects the settlement, lateral deformation, and pore pressure predictions. The objective of this research was to improve the prediction of soil behavior based on high-quality field data by using state of the art vacuum preloading simulations. The results were compared with those of a series of instrumentation equipment, i.e. a settlement plate, an extensometer, and a piezometer. This research used data from the Palembang-Indralaya Toll Road, a section of the Trans Sumatera Toll Road that is approximately 22 km long and has an embankment height of about 4 m to 9 m. It was built over a swampy soft soil area, using vacuum preloading to improve the soil. Axisymmetric analysis of vacuum preloading was conducted for a single-drain system, plane-strain analysis was conducted for single- and multiple-drain systems, and 3D analysis was conducted for single-drain, multiple-drain, and cluster-drain systems. The results show that the proposed method produced a good correlation between the predicted data and the recorded monitoring data.